Characteristics of Flavor Enhancer Based on Moringa Leaves and Tempeh Using Protease Enzymes From Sap of Papaya and Crown Flower - Prayoga, Dewa Gede Eka; Wartini, Ni Made; Permana, I Dewa Gde Mayun (Food, Agriculture and Natural Resources - NETWORKS, 2023)
Flavor enhancer is a food additive that's designed to enhance flavor. This research aims to determine the effect type (papaya, crown flower, and mixed protease) and percentage addition (1%, 2%, and 3%) of enzyme on the characteristics of flavor enhancer based on moringa leaves and tempeh. The design used in this study was a completely randomized design in factorial pattern. The variables observed included the degree of hydrolysis, moisture content, soluble protein content, maillard product, water solubility index, oil absorption, and glutamic acid content. Data were analyzed by Analysis of Variance (ANOVA) and followed by Duncan's test. The results showed that the interaction between the type and percentage addition of enzyme had a very significant effect on the degree of hydrolysis, maillard product, and glutamic acid content, significantly affected the soluble protein content and water solubility index, and had no significant effect on water content and oil absorption. The treatment type and percentage addition of enzyme had a very significant effect on the degree of hydrolysis, soluble protein content, maillard product, water solubility index, oil absorption and glutamic acid content, and had no significant effect on water content. Hydrolysis using mixed protease enzymes with an addition percentage of 3% produced flavor enhancer that had the best characteristics based on the highest glutamic acid content of 30.583 mg/g glutamic acid equivalent with a degree of hydrolysis of 65.781%, moisture content of 5.096%, soluble protein content of 1.529 mg/g tyrosine equivalent, maillard product of 0.221 AU, water solubility index of 0.0980 g/mL, and oil absorption of 1.55 mL/g. Keywords— hydrolysis, protease, flavor enhancer, moringa leaves, tempeh